Tissue reactions under piezoelectric shockwave application for the fragmentation of biliary calculi. Issue 5 (May 1989) - Ell, C; Kerzel, W; Heyder, N; Rödl, W; Langer, H; Mischke, U; Giedl, J; Domschke, W
Abstract : The tissue reactions that occurred during piezoelectric shockwaves for the fragmentation of biliary calculi were investigated in 10 surgically removed stone containing human gall bladders and in acute (six dogs) and chronic (six dogs) animal experiments. Before and after shockwave (500, 1500 or 3000) in the anaesthetised dogs, computed tomography (CT), magnetic imaging (MRI) and laboratory tests were done; treatment was carried out under continuous ultrasonographic control. Shockwave applications to the human gall bladders resulted in disintegration of the stones with no macroscopically or microscopically detectable tissue changes. In acute animal experiments, small haematomas were observed in all six animals at surfaces, but also inside the liver and gall bladder (max diameter 25 mm). Perforation or intra-abdominal or pleural bleeding did not occur. In chronic experiments, no macroscopic, and only slight microscopic residual lesions (haemosiderin deposits) were seen three weeks after shockwave. In almost all instances, the lesions were detected by CT, MRI, and ultrasonography, while laboratory tests were negative.